Sleep-disordered breathing and the risk of Alzheimer's disease. (February 2021) - Liguori, Claudio; Maestri, Michelangelo; Spanetta, Matteo; Placidi, Fabio; Bonanni, Enrica; Mercuri, Nicola B.; Guarnieri, Biancamaria
Summary: Sleep-disordered breathing is highly prevalent in the elderly population. Obstructive sleep apnea (OSA) represents the most common sleep disorder among the adult and elderly population. Recently, OSA diagnosis has been associated with an increased risk of developing cognitive decline and dementia, including vascular dementia and Alzheimer's disease (AD). Subsequently, there have been studies on AD biomarkers investigating cerebrospinal fluid, blood, neuroimaging, and nuclear medicine biomarkers in patients with OSA. Furthermore, studies have attempted to assess the possible effects of continuous positive airway pressure (CPAP) treatment on the cognitive trajectory and AD biomarkers in patients with OSA. This review summarizes the findings of studies on each AD biomarker (cognitive, biofluid, neuroimaging, and nuclear medicine imaging) in patients with OSA, also accounting for the related effects of CPAP treatment. In addition, the hypothetical model connecting OSA to AD in a bi-directional interplay is analyzed. Finally, the sex-based differences in prevalence and clinical symptoms of OSA between men and women have been investigated in relation to AD risk. Further studies investigating AD biomarkers changes in patients with OSA and the effect of CPAP treatment should be auspicated in future for identifying strategies to prevent the development of AD.